Effectiveness of Lymph Node Dissection in Women over Age 70 with Stage I Ovarian Cancer - Genping Huang; Guoping Zhu; Cheng Chen (IMR Press, 2024)
Background: Considering the possibility of surgical intervention affecting the survival benefit of elderly patients, the relationship between lymph node dissection and the survival of elderly patients with stage I ovarian cancer (OC) was retrospectively analyzed. Methods: This was a retrospective cohort study using the database in Surveillance, Epidemiology and End Results (SEER) which was queried to identify 8191 women with stage I OC treated with surgery from 1975 to 2016. Frequencies and percentages were presented to describe the categorical data. Pearson χ2 test was used to compare the correlation between the patient characteristics and lymph node dissection. Kaplan-Meier test was used to analyze the relationship between overall survival (OS) and patients at all age levels. The log-rank test was used for pairwise comparisons of OS. Cox proportional hazard regression analyses were performed to determine the association between lymph node dissection status and the OS in women with stage I OC. Results: There were 8191 stage I OC patients in this study. Among all patients undergoing lymph node dissection, 11.23% patients were older than 70 years. However, 17.44% of the patients over 70 years of age did not undergo lymph node dissection. Lymph node conservation was associated with a higher mortality risk compared to lymph node dissection. Kaplan-Meier analysis revealed that patients had a worse prognosis with lymph node conservation in people older than 70 years. Univariate and multivariate analysis showed that age and lymph node dissection both remained independent prognostic factors for improved OS with stage I OC. Conclusions: Lymph node dissection was an independent predictor of improved long-term OS in stage I OC patients and had a significant benefit in women over age 70.